John Rawls and the theory of justice - Flores Morales, Jorge Alberto (2017)
The issue of justice is one of the principles that every organized society seeks to achieve in view of the common good of the majority of its citizens. However, what happens when this principle is not realized? What part of the social contract suffers from the breaking of this principle and of others? Rawls seeks to answer these questions and to formulate a theory of justice in search of a just society based on freedom and obligations to others and to oneself.